Hypokalemia during the early phase of refeeding in patients with cancer (Clinics, 2013)
OBJECTIVE: Refeeding syndrome occurs in patients with severe malnutrition when refeeding begins after a long period of starvation. This syndrome increases the risk of clinical complications and mortality. Hypophosphatemia is considered the primary characteristic of the syndrome. The aim of our study was to investigate the presence of other electrolyte alterations in patients with cancer during the early stage of refeeding. METHODS: In this observational study, we enrolled 34 patients with cancer of the upper aerodigestive tract receiving upfront radiotherapy who were also enrolled in a nutrition program. A caloric intake assessment, anthropometric measurements and biochemical laboratory tests were performed. RESULTS: Significant weight loss (∼20%) was found in these patients. In the patients receiving artificial nutrition, we found lower levels of potassium and total protein compared with those who were fed orally (p = 0.03 for potassium and 0.02 for protein, respectively). Patients on enteral tube feeding had a higher caloric intake compared with those who were fed orally (25±5 kcal/kg/day vs. 10±2 kcal/kg/day). CONCLUSION: Hypokalemia, like hypophosphatemia, could be a complication associated with refeeding in patients with cancer. Hypokalemia was present in the early stages of high-calorie refeeding.